Acciones que afectan la etica del contador publico en colombia entre los años 2019 y 2021 (2023)
The ethics of the public accountant is a constantly discussed aspect in Colombian higher education, taking into account the countless corrupt situations that Colombian society faces in accounting, tax and financial matters. For this reason, the objective of the research was to identify the factors that influence the trend towards unethical actions by public accountants in Colombia according to research carried out during the years 2019-2021. The methodology consisted of a qualitative approach of documentary design and descriptive type, with 20 investigations consulted in information sources from 2019 to 2021. The results based on three variables that were, incidence of the ethical teaching of the public accountant, principles and values of the public accountant violated in Colombia and the ethical training needs of the Colombian public accountant, reflected the impact of education in the consolidation of ethical attitudes in public accountants, the violation of principles such as responsibility, objectivity, respect between colleagues, independence, integrity and observation of regulatory provisions, an issue for which it is a challenge for higher education to train professionals in values that recognize the incidence of their actions in society, through the transversality of ethics.